Five-component, one-pot synthesis of an electroactive rotaxane comprising a bisferrocene macrocycle - Lagesse, Natalie; Pisciottani, Luca; Douarre, Maxime; Godard, Pascale; Kauffmann, Brice; Martí-Centelles, Vicente; McClenaghan, Nathan D. (Beilstein Journal of Organic Chemistry, 2020)
The templated clipping of a ferrocene-grafted isophthalic acid derivative to encircle a hydrogen-bonding axle through the reaction with 1,4-bis(aminomethyl)benzene is described. The constituent electroactive macrocycle of the resultant [2]rotaxane is a homologue of the versatile benchmark tetraamide variant developed by Leigh and co-workers. The relative templating effect of different hydrogen-bonding motifs in rotaxane and pseudorotaxane generation is compared, with yields varying from 0 to 41%. The electrochemical properties and single crystal X-ray structure of a doubly ferrocene-decorated [2]rotaxane are further reported.
Keywords: ferrocene; macrocycle; rotaxane; single crystal X-ray structure; template

The Nature of the Mechanical Bond: From Molecules to Machines - Bruns, C. J.; Stoddart, J. F. (John Wiley and Sons, 2017)

(untitled) - Bissell, R. A.; Córdova, E.; Kaifer, A. E.; Stoddart, J. F. (Nature, 1994)

Electrochemistry of Functional Supramolecular Systems - Credi, A.; Venturi, M. (Electroactive rotaxanes and catenanes, 2010)

(untitled) - Altieri, A.; Bottari, G.; Dehez, F.; Leigh, D. A.; Wong, J. K. Y.; Zerbetto, F. (Angew. Chem., Int. Ed., 2003)

(untitled) - Martinez-Cuezva, A.; Rodrigues, L. V.; Navarro, C.; Carro-Guillen, F.; Buriol, L.; Frizzo, C. P.; Martins, M. A. P.; Alajarin, M.; Berna, J. (J. Org. Chem., 2015)

(untitled) - Leigh, D. A.; Marcos, V.; Nalbantoglu, T.; Vitorica-Yrezabal, I. J.; Yasar, F. T.; Zhu, X. (J. Am. Chem. Soc., 2017)

(untitled) - Panman, M. R.; Bakker, B. H.; den Uyl, D.; Kay, E. R.; Leigh, D. A.; Buma, W. J.; Brouwer, A. M.; Geenevasen, J. A. J.; Woutersen, S. (Nat. Chem., 2013)

(untitled) - Fernandes, A.; Viterisi, A.; Aucagne, V.; Leigh, D. A.; Papot, S. (Chem. Commun., 2012)

(untitled) - Tron, A.; Pianet, I.; Martinez-Cuezva, A.; Tucker, J. H. R.; Pisciottani, L.; Alajarin, M.; Berna, J.; McClenaghan, N. D. (Org. Lett., 2017)

(untitled) - Martinez-Cuezva, A.; Marin-Luna, M.; Alonso, D. A.; Ros-Ñiguez, D.; Alajarin, M.; Berna, J. (Org. Lett., 2019)

(untitled) - Hernandez, J. V.; Kay, E. R.; Leigh, D. A. (Science, 2004)

(untitled) - Leigh, D. A.; Wong, J. K. Y.; Dehez, F.; Zerbetto, F. (Nature, 2003)

(untitled) - Berná, J.; Leigh, D. A.; Lubomska, M.; Mendoza, S. M.; Pérez, E. M.; Rudolf, P.; Teobaldi, G.; Zerbetto, F. (Nat. Mater., 2005)

(untitled) - Brouwer, A. M.; Frochot, C.; Gatti, F. G.; Leigh, D. A.; Mottier, L.; Paolucci, F.; Roffia, S.; Wurpel, G. W. H. (Science, 2001)

(untitled) - Gatti, F. G.; Leigh, D. A.; Nepogodiev, S. A.; Slawin, A. M. Z.; Teat, S. J.; Wong, J. K. Y. (J. Am. Chem. Soc., 2001)

(untitled) - Martinez-Cuezva, A.; Morales, F.; Marley, G. R.; Lopez-Lopez, A.; Martinez-Costa, J. C.; Bautista, D.; Alajarin, M.; Berna, J. (Eur. J. Org. Chem., 2019)

(untitled) - Martí-Centelles, V.; Burguete, M. I.; Luis, S. V. (J. Org. Chem., 2016)

(untitled) - Martí-Centelles, V.; Burguete, M. I.; Cativiela, C.; Luis, S. V. (J. Org. Chem., 2014)

(untitled) - Martí-Centelles, V.; Pandey, M. D.; Burguete, M. I.; Luis, S. V. (Chem. Rev., 2015)

(untitled) - Berná, J.; Alajarín, M.; Martínez-Espín, J. S.; Buriol, L.; Martins, M. A. P.; Orenes, R.-Á. (Chem. Commun., 2012)

(untitled) - Pavlishchuk, V. V.; Addison, A. W. (Inorg. Chim. Acta, 2000)

(untitled) - Pisciottani, L.; Douarre, M.; Bibal, B.; Davies, C.; Roberts, H.; Kauffmann, B.; Horswell, S. L.; Tucker, J. H. R.; McClenaghan, N. D. (Supramol. Chem., 2018)

An introduction to hydrogen bonding - Jeffrey, G. A. (Oxford University Press, 1997)

(untitled) - Evans, N. H.; Rahman, H.; Leontiev, A. V.; Greenham, N. D.; Orlowski, G. A.; Zeng, Q.; Jacobs, R. M. J.; Serpell, C. J.; Kilah, N. L.; Davis, J. J.; Beer, P. D. (Chem. Sci., 2012)

(untitled) - Liu, W.; Zheng, H.; Du, L.; Chen, B.; Song, M. (Z. Anorg. Allg. Chem., 2010)

(untitled) - Dellinger, J. A.; George, G. D.; Roberts, C. W. (J. Polym. Sci., Polym. Lett. Ed., 1978)

(untitled) - Dolomanov, O. V.; Bourhis, L. J.; Gildea, R. J.; Howard, J. A. K.; Puschmann, H. (J. Appl. Crystallogr., 2009)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. A: Found. Adv., 2015)

(untitled) - Sheldrick, G. M. (Acta Crystallogr., Sect. C: Struct. Chem., 2015)

Spartan 18, build 1.3.0 (Wavefunction Inc., 2019)